Pengaruh Energi Terbarukan, Emisi CO₂, dan PMTB terhadap Pertumbuhan Ekonomi Negara OECD - Muhammad Taufiqurrahman Afrendi; Ambya .; Muhammad Mufti Hudani (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Economic expansion continues to serve as a crucial measure of a nation's progress, while shifting towards renewable energy sources and decreasing carbon emissions has emerged as a vital goal for OECD nations in their pursuit of sustainable development. This research intends to analyze the influence of renewable energy usage, carbon dioxide (CO₂) emissions, and Gross Fixed Capital Formation (GFCF) on economic growth, as indicated by Gross Domestic Product (GDP), within OECD countries from 2015 to 2024. A quantitative methodology was utilized, employing panel data regression analysis based on annual secondary data sourced from the World Bank. The research targeted OECD member states, with the sample chosen through purposive sampling, taking into account the availability and thoroughness of the data. The results indicate that the consumption of renewable energy, CO₂ emissions, and Gross Fixed Capital Formation all exert a positive and statistically significant impact on economic growth. These outcomes suggest that the adoption of renewable energy and capital investments play a role in fostering economic growth, while the correlation between CO₂ emissions and GDP implies that economic growth within OECD nations is still heavily tied to carbon-heavy production methods. The results suggest that measures aimed at bolstering renewable energy initiatives and enhancing productive investments should be reinforced, alongside hastening the shift towards a low-carbon economic model to ensure sustainable economic growth.